Lithium Perchlorate Catalyzed Electrophilic Activation: A Convenient One-pot Synthesis of trans-Cinnamic Acids - Kaur, Paranjeet; Khatik, Gopal L. (Letters in Organic Chemistry, 2018)
Background: Currently perchlorate catalysts gain much attention in organic synthesis due to ease of operation, wide applicability, high yield, and economy. This is evident through increasing number of citation related to their application in industry as well as other allied fields. The aim of this paper is to describe a methodology using lithium perchlorate to catalyze the Knoevenagel condensation reaction for the synthesis of biologically active trans-cinnamic acid in good to excellent yield. Methods: We discuss herein an economic, user-friendly one-pot synthesis of trans-cinnamic acids by refluxing a mixture of a malonic acid with aryl aldehyde in pyridine. The product was easily isolated via filtration and thereafter washed and characterized by spectroscopic methods. Results: This method is robust, stereoselective and high yielding. It can be utilized to synthesize a wide array of trans-cinnamic acids in good to excellent yield using 20% of lithium perchlorate catalyst. It is also useful in the synthesis of aliphatic α,β-unsaturated carboxylic acid. Conclusion: The role of lithium perchlorate as a mild catalyst in the synthesis of trans-cinnamic acid was explored. The reactions afforded a good yield of various products with simpler isolation.
Keywords: Lithium perchlorate